2015
DOI: 10.1017/s104795111500150x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of atherogenic risk factors among poorly controlled and well-controlled adolescent phenylketonuria patients

Abstract: Lower high-density lipoprotein cholesterol and higher homocysteine and mean platelet volume levels were detected in phenylketonuria patients. In particular, these changes were more prominent in well-controlled patients. We conclude that phenylketonuria patients might be at risk for atherosclerosis, and therefore screening for atherosclerotic risk factors should be included in the phenylketonuria therapy and follow-up in addition to other parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…Another study [20] in 59 patients with PKU and 44 healthy controls (11 to 17 years of age) found significantly lower levels of cardioprotective HDL cholesterol in well-controlled ( n = 24; blood Phe < 360 μmol/L) vs poorly-controlled ( n = 35; blood Phe > 360 μmol/L) PKU patients; both groups were significantly lower than non-PKU controls. Additionally, higher levels of homocysteine and increased mean platelet volume levels were also observed in PKU patients vs healthy controls and differences in these parameters were more evident in poorly-controlled PKU patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another study [20] in 59 patients with PKU and 44 healthy controls (11 to 17 years of age) found significantly lower levels of cardioprotective HDL cholesterol in well-controlled ( n = 24; blood Phe < 360 μmol/L) vs poorly-controlled ( n = 35; blood Phe > 360 μmol/L) PKU patients; both groups were significantly lower than non-PKU controls. Additionally, higher levels of homocysteine and increased mean platelet volume levels were also observed in PKU patients vs healthy controls and differences in these parameters were more evident in poorly-controlled PKU patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…In other pathologic conditions, ECM/BCM ratio has positively correlated with risk of death in dialysis patients [19] , while PA has been negatively affected by nutritional imbalances, thus used as a prognostic factor in patients with homocystinuria [20] and cancer [21] . Both ECM/BCM ratio and PA values have been related to increased inflammation [17] , [18] , [19] , [21] , which are seen in several pathological processes including in PKU patients [37] , [38] . Because nutritional imbalances have shown to underlie increased inflammation [23] , [24] , the Phe-restricted diet could represent a threat to the overall health of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis for folic acid the excessively high heterogeneity across the studies undermined its reliability to draw a conclusion on between group differences in status. Nonetheless 6 of the 7 studies [ 84 89 ] had confidence intervals on the right side of the plot (Fig. 6 ), suggesting positive differences between PKU patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%